A weighted random forests approach to improve predictive performance. (8th July 2013) - Winham, Stacey J.; Freimuth, Robert R.; Biernacka, Joanna M.
Abstract Identifying genetic variants associated with complex disease in high‐dimensional data is a challenging problem, and complicated etiologies such as gene–gene interactions are often ignored in analyses. The data‐mining method random forests (RF) can handle high dimensions; however, in high‐dimensional data, RF is not an effective filter for identifying risk factors associated with the disease trait via complex genetic models such as gene–gene interactions without strong marginal components. In this article we propose an extension called weighted random forests (wRF), which incorporates tree‐level weights to emphasize more accurate trees in prediction and calculation of variable importance. We demonstrate through simulation and application to data from a genetic study of addiction that wRF can outperform RF in high‐dimensional data, although the improvements are modest and limited to situations with effect sizes that are larger than what is realistic in genetics of complex disease. Thus, the current implementation of wRF is unlikely to improve detection of relevant predictors in high‐dimensional genetic data, but may be applicable in other situations where larger effect sizes are anticipated. © 2013 Wiley Periodicals, Inc. Statistical Analysis and Data Mining, 2013